Realisasi dan hambatan peran ayah ditinjau dalam perspektif pendidikan seks anak usia 3 – 6 tahun di Kelurahan Kebon Jeruk - Rahmah, Aisyah Nur; Tasu'ah, Neneng (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2024)
The phenomenon of sexual harrasment is rampant at this time. The importance of introducing early childhood sex education as an effort to prevent more victims and perpetrators of sexual deviance. Fathers as leaders contribute to being responsible for providing protection and education regarding sex education for their children. This study aims to determine the realization of the role and obstacles of fathers from the perspective of sex education for children aged 3 – 6 years in Kelurahan Kebon Jeruk. This study used a descriptive qualitative research approach. Data collection techniques used observation, interview, and documentation methods. This study involved 6 main informants who are fathers of children aged 3 – 6 years. Data validity techniques used source triangulation and technique triangulation. The results showed that the realization of the father’s role in the perspective of sex education for children aged 3 – 6 years, namely the realization of fathers’s role as a protector in sex education is shown by (a) Creating a safe environment for sex education for children age 3 – 6 years, (b) Scheduling children’s play activities to prevent potential dangers, (c) Supervising the use of media and the internet to avoid adult content. The realization of the father’s role as an educator in sex education is shown by (a) Cooperation beetween father and mother in sex education for children aged 3 – 6 years, (b) Providing sex education information according to the understanding of children aged 3 – 6 years. Another finding of this study is the existence of father’s obstacles in providing sex education for children aged 3 – 6 years, namely (1) Father’s ignorance in the process of delivering sex education to children, (2) Gender diffrences between fathers and daughters, and (3) Father’s perception that children are not ready to be discussed about sex.